Práticas estratégicas e a teoria da dotação social estratégica : um estudo de caso em uma Startup - Saes, Danillo Xavier (2015)
Due the fact that the Strategy theme is considered multidisciplinary, studies about this subject are diversified. Over time, this topic has gained a more specific research vision where authors seek their understanding by a praxeological vision, in other words, focused on the activities of organizational actors. This line of research is called Strategy as Practice. In this context, Maciel (2011) developed a theory called Theory of Strategic Social Endowing (TDSE), which seeks to understand how the strategies and its practitioners are socially built. In addition, the author discusses about the presence of the discourse of strategic social endowing, present in social arenas that individuals are inserted in their life story. Based on this substantive theory through survey descriptive and qualitative methods using semi-structured interview, document analysis and observation nonparticipants, this study aims to analyze how the strategic social endowing of organizational actors can influence the strategic practice of a Startup in the city of Maringa (Brazil). The focus of this research was based on the investigated organization's characteristics, due to its similarity to the organization researched during the development of TDSE (MACIEL, 2011). With the research conduct, we found the non uniqueness of the theory, and the Strategic Social Endowing (DSE) and his speech can provide explanations of the way the strategic practice are influenced by the strategic endowing of the organization's social actors.